2003
DOI: 10.1165/rcmb.2002-0124oc
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinase-3 Downregulation in Lymphangioleiomyomatosis

Abstract: Pulmonary lymphangioleiomyomatosis (LAM) is characterized by abnormal smooth muscle-like cell proliferation leading to tissue destruction and cyst formation. We demonstrate that serum response factor (SRF), a critical smooth muscle transcription factor, is overexpressed in LAM cells. To determine whether abnormal SRF levels might have a pathogenic role in LAM, we transfected SRF into mouse lung fibroblasts and performed a cDNA array analysis. High SRF level upregulated the expression of matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 45 publications
4
39
0
2
Order By: Relevance
“…Elevated levels of SRF have been reported in lymphangioleiomyomatosis (LAM), a rare disorder of interstitial pulmonary SMCs. 95 Induced SRF expression resulted in the upregulation of two matrix metalloproteinases (2 and 14) and a reduction in one of the inhibitors of metalloproteinases (TIMP3), all of which are characteristic of LAM. 95 As with other putative targets, whether these effects are directed through SRF-binding CArG elements is unknown.…”
Section: Srf and Pulmonary System Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of SRF have been reported in lymphangioleiomyomatosis (LAM), a rare disorder of interstitial pulmonary SMCs. 95 Induced SRF expression resulted in the upregulation of two matrix metalloproteinases (2 and 14) and a reduction in one of the inhibitors of metalloproteinases (TIMP3), all of which are characteristic of LAM. 95 As with other putative targets, whether these effects are directed through SRF-binding CArG elements is unknown.…”
Section: Srf and Pulmonary System Diseasementioning
confidence: 99%
“…95 Induced SRF expression resulted in the upregulation of two matrix metalloproteinases (2 and 14) and a reduction in one of the inhibitors of metalloproteinases (TIMP3), all of which are characteristic of LAM. 95 As with other putative targets, whether these effects are directed through SRF-binding CArG elements is unknown. In hypoplastic lungs of humans, where a stretch signal known to promote alternate SRF splice variants favoring normal pulmonary myogenesis is thought to be missing, the levels of full-length SRF are reduced.…”
Section: Srf and Pulmonary System Diseasementioning
confidence: 99%
“…These include expression of MMP-2, 20-22 MMP-2 activator, membrane type (MT) MT-1-MMP or MMP-14, [22][23][24] and MMP9. 21 The tissue inhibitors of metalloproteinase TIMP-1, TIMP À 2, and TIMP À 3 were expressed at low level in LAM cells.…”
Section: Expression Of Metalloproteinases (Mmps) and Circulation Of Lmentioning
confidence: 99%
“…21 The tissue inhibitors of metalloproteinase TIMP-1, TIMP À 2, and TIMP À 3 were expressed at low level in LAM cells. 21,22 Doxycycline treatment to block MMP activity resulted in an improvement in the respiratory function of one patient. 25 A recent study by Lee et al found that cells derived from a LAM-associated angiomyolipoma exhibited higher of MMP2 activity, and that this was not sensitive to rapamycin, suggesting mTORC1-independence.…”
Section: Expression Of Metalloproteinases (Mmps) and Circulation Of Lmentioning
confidence: 99%
“…LAM cells are smooth muscle-like, express melanocytic proteins, and grow in a diffuse pattern throughout both lungs (4)(5)(6). The relationship between the LAM cells and the regions of cystic lung degeneration is unknown, although it is believed that secretion of proteases by LAM cells is a contributing factor (6)(7)(8)(9)(10)(11)(12).…”
Section: Lymphangioleiomyomatosis and The Tuberous Sclerosis Complex mentioning
confidence: 99%